Law and order in ancient Athens / Adriaan Lanni. - Lanni, Adriaan, 1972- (Cambridge University Press, 2016)
The classical Athenian 'state' had almost no formal coercive apparatus to ensure order or compliance with law: there was no professional police force or public prosecutor, and nearly every step in the legal process depended on private initiative. And yet Athens was a remarkably peaceful and well-ordered society by both ancient and contemporary standards. Why? Law and Order in Ancient Athens draws on contemporary legal scholarship to explore how order was maintained in Athens. Lanni argues that law and formal legal institutions played a greater role in maintaining order than is generally acknowledged. The legal system did encourage compliance with law, but not through the familiar deterrence mechanism of imposing sanctions for violating statutes. Lanni shows how formal institutions facilitated the operation of informal social control in a society that was too large and diverse to be characterized as a 'face-to-face community' or 'close-knit group'.